The abundance and diversity of the seagrass ecosystem in Cancabato Bay. - Juntilla, Jackie Mae R. (Jackie Mae R. Juntilla, 2018)
Seagrasses are known to be the only flowering plants to recolonize the sea. They ar utilized as the nursery grounds for many marine organisms and serves as the carbon sink. On the month October, 2018, a study was conducted to determine the abundance and diversity of the seagrass ecosystem in Cancabato Bay Tacloban City. During the reconnaissance study, four sampling sites were established based on the status of the seagrass beds. These include Brgy. Cataisan San Jose, Fatima Village, and Magallanes (San Fernando). Quadrats with 0.5x0.5 meter square were randomly thrown to collect seagrass samples and record the number of species covered. Brgy. Cataisan had the most diverse species consisting of Cymodocea serrulata, Enhalus acoroides, Halodule uninervis, and Thalassia hemprichii. Among these species, C. serrulata had the highest percent cover of 89.6 plus/minus 3.58. On the other hand, Fatima Village had the most abundant E. acoroides species with an average biomass of 85.98 g/meter square DW. It was observed that plant's own morphology, substrate type, water currents and temperature can affect the growth and distribution of seagrass species. Likewise, anthropogenic factors such as fish pens, docked boats, siltation, and collection of bivalves serve as threats to the seagrass ecosystem. Furthermore, studies must be conducted in order to gain knowledge in restoring and preserving the seagrass ecosystem.